Safety Evaluation of Osun River Water Containing Heavy Metals and Volatile Organic Compounds (VOCs) in Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study evaluated the pH, heavy metals and volatile organic compounds (VOCs) in Osun river water. It also evaluated its safety in rats. Heavy metals were determined by atomic absorption spectrophotometry (AAS) while VOCs were determined by gas chromatography coupled with flame ionization detector (GC-FID). Male and female rats were exposed to Osun river water for three weeks and then sacrificed. The abundance of heavy metals in Osun river followed the trend Pb > Cd > Zn > Fe > Cr > Cu while VOCs followed the trend benzene < ethylbenzene < toluene < xylene. The concentrations of Pb, Cd and benzene were higher than the permissible limits of Standards Organization of Nigeria (SON) and World Health Organization (WHO) respectively. Rats exposed to Osun river water for three weeks had increased WBC, thiobarbituric acid reactive substances (TBARS), serum proteins and serum aminotransferases. There were also significant decreases (P < 0.05) in HCT, PLT, liver aminotransferases and liver glutathione compared to the control. These results show that the pollutants in Osun river water are capable of inducing hematological imbalance and liver cell injury. The toxicity induced in blood was sex-dependent affecting female rats more than male rats.
Keywords: Osun river; Haematology; Biochemical parameters; Heavy metals; Volatile Organic Compounds